Evaluation of Usability, User Experience and Accessibility of Applications: a Tertiary Review - Piedra Pacheco, Antonio Jesús (2024)
In the present time, there is a growing need to understand how users interact with digital applications to ensure the success of new products and a good experience for the users. Three main concepts are central to this subject: usability, user experience, and accessibility. As such research efforts have been undertaken to create evaluation instruments for each and apply them to multiple tools. This study aims to perform a compilation of the research gathered in multiple secondary studies on the subject of evaluating these concepts. A systematic search process was performed to answer research questions related to how evaluations in the field of usability, user experience, and accessibility are performed. From this search 45 secondary studies were obtained and further analyzed. We were able to identify the most common methodologies and tools highlighted across the secondary studies for each concept. The main results found were the following: questionnaires are ubiquitous in the field of user experience evaluation and to a lesser extent for usability while accessibility evaluation is mostly performed with the aid of automated tools, there is a tendency for authors to develop and use their own questionnaires without validating them and 24 main categories for the evaluated characteristics were found, of which Satisfaction, Efficiency, Effectiveness, and Attractiveness were the most common.